2013
DOI: 10.1200/jop.2013.001025
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Tobacco Use in Patients With Cancer: A Survey of American Society of Clinical Oncology Members

Abstract: Purpose: Assessing tobacco use and providing cessation support is recommended by the American Society for Clinical Oncology (ASCO). The purpose of this study was to evaluate practice patterns and perceptions of tobacco use and barriers to providing cessation support for patients with cancer. Methods:In 2012, an online survey was sent to 18,502 full ASCO members asking about their practice patterns regarding tobacco assessment, cessation support, perceptions of tobacco use, and barriers to providing cessation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 28 publications
(28 reference statements)
10
155
1
Order By: Relevance
“…Even though 70% of cancer patients who smoke are motivated to quit smoking, only 56% of physicians recommend that their cancer patients who smoke stop smoking 52 and most oncology providers do not provide smoking interventions beyond advice to quit. 53 Our work 54 and the work of others [55][56][57][58][59] have shown that the major barriers to providers implementing smoking cessation services included lack of expertise and time. Education programs for health care providers as well as dedicated smoking cessation programs would improve tobacco treatment for cancer patients.…”
Section: Discussionmentioning
confidence: 94%
“…Even though 70% of cancer patients who smoke are motivated to quit smoking, only 56% of physicians recommend that their cancer patients who smoke stop smoking 52 and most oncology providers do not provide smoking interventions beyond advice to quit. 53 Our work 54 and the work of others [55][56][57][58][59] have shown that the major barriers to providers implementing smoking cessation services included lack of expertise and time. Education programs for health care providers as well as dedicated smoking cessation programs would improve tobacco treatment for cancer patients.…”
Section: Discussionmentioning
confidence: 94%
“…About half of cancer patients who smoked prior to diagnosis continue to smoke [23]. [25]; yet, only 40% of oncologists discuss medications with patients who smoke and only 38% actively treat their patients for tobacco dependence [26]. Critical opportunities to improve oncological outcomes and extend patient survival are being missed.…”
Section: Smoking Cessation Treatment In Cancer Patientsmentioning
confidence: 99%
“…Two recent international surveys of cancer specialists found that less than one-half routinely offered patients smoking cessation treatment; common concerns were that intervention would be ineffective, and cancer patients would resist treatment. 18,19 Even so, we have previously reported that patients treated surgically for lung cancer express a wish for much greater involvement of clinicians a Cancer subgroup patients and matched CHD control patients: lung, n = 2,340; bladder, n = 944; UAT, n = 422.…”
Section: Interpretation Of Findings and Comparison With Existing Studiesmentioning
confidence: 99%
“…Support for smoking cessation in secondary care is low, however, and it is unlikely to be the main source of cessation support. [17][18][19][20] As with all studies based on health care records, it is possible that the general practitioners provided advice to quit or on how to quit which they did not record. Although underreporting would underestimate the true rate of intervention, it is likely to underestimate the frequency of intervention in patients with cancer and CHD equally and is thus an implausible explanation for the findings.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation